Clinical Efficacy of Single- vs Dual-Level Transversus Abdominis Plane Block for Lower Segment Cesarean Section: A Prospective, Randomized, Controlled Study - Cao WN; Qiu B; Li Y; Hu CL; Liu HC; Yuan KM; Wang FY (Journal of Pain Research)
Wan-Na Cao,1,2 Bei Qiu,1 Ying Li,1 Chang-Long Hu,1 Hua-Cheng Liu,2 Kai-Ming Yuan,1,2 Fang-Yi Wang1,2 1Department of Anesthesiology, Taizhou Women and Children’s Hospital of Wenzhou Medical University, Taizhou, 318000, People’s Republic of China; 2Department of Anesthesiology and Perioperative Medicine, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Key Laboratory of Pediatric Anesthesiology, Ministry of Education, Wenzhou Medical University, Key Laboratory of Anesthesiology of Zhejiang Province, Wenzhou Medical University, Wenzhou, 325027, People’s Republic of ChinaCorrespondence: Fang-Yi Wang, Email wangfy0229@163.com Kai-Ming Yuan, Email yuankm@wmu.edu.cnObjective: Transversus abdominis plane block (TAPB) has been widely used for lower-segment cesarean sections (CS). However, traditional single-level TAPB may not provide sufficient analgesia for parturients. This study aimed to validate whether dual-level TAPB could offer more extensive blocking and better clinical outcomes.Methods: A total of 114 full-term parturients undergoing lower-segment CS were included in this prospective, randomized, controlled study. Subjects were randomly assigned to receive either single-level (group SL) or dual-level (group DL) TAPB. Dual-level TAPB was performed at the umbilical level and the level above the anterior superior iliac spine, while single-level was performed only at the umbilical level. The primary outcome was the proportion of the abdomen successfully blocked 20 minutes after TAPB.Results: Twenty minutes after TAPB, dual-level TAPB resulted in a more extensive cutaneous sensory block compared to single-level TAPB. The difference in the proportion of successfully blocked zones was statistically significant, with 46.9% (43.8%, 53.1%) in group SL versus 71.9% (62.5%, 75.0%) in group DL, p < 0.001. Notably, the proportion of parturients with the “surgical area” completely blocked was significantly higher in group DL (94.7%) than in group SL (82.5%) (p = 0.039). Compared to Group SL, the first request for postoperative analgesia was delayed in Group DL by 2.5 hours.Conclusion: Compared to traditional single-level TAPB, dual-level TAPB produced more extensive cutaneous sensory block and better postoperative analgesia effects.Keywords: block range, opioid consumption, visual analog scale